1984
DOI: 10.1016/0166-4328(84)90035-4
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal EEG and motor activity in the cat: The role of eye movements and body acceleration

Abstract: Key words: hippocampus EEG -motor behaviour -vestibular inputs -eye movements -rhythmic slow activity (theta rhythm) -catIn cat the relation between various behaviours and the spectral properties of the hippocampal EEG was investigated. Both EEG and behaviour were quantified and results were evaluated statistically. Significant relationships were found between the properties of the hippocampal EEG and motor acts (walking, sitting, eating, stepping and eye movements). These results were compared with those obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…These studies indicated that theta band (6-9 Hz) rhythm was correlated to behaviors including locomotion and whole body movements ( Vanderwolf, 1969;Oddie and Bland, 1998;Miller, 1991). A sensory contribution to HF theta waves has also been reported in a previous study in which cats were restrained, and passively translated along a linear path in an illuminated room (Arnolds et al, 1984). Unit recording studies also indicated that running velocity of the animal affected activity of HF pyramidal and interneurons Hirase et al, 1999).…”
Section: Introductionmentioning
confidence: 79%
“…These studies indicated that theta band (6-9 Hz) rhythm was correlated to behaviors including locomotion and whole body movements ( Vanderwolf, 1969;Oddie and Bland, 1998;Miller, 1991). A sensory contribution to HF theta waves has also been reported in a previous study in which cats were restrained, and passively translated along a linear path in an illuminated room (Arnolds et al, 1984). Unit recording studies also indicated that running velocity of the animal affected activity of HF pyramidal and interneurons Hirase et al, 1999).…”
Section: Introductionmentioning
confidence: 79%
“…Similar patterns of amplitude and frequency changes have been previously reported by Elazar and Adey (1967) in cats, during what the authors described as a tense state before movement toward food reward. Arnolds et al (1984) observed that in the cat, amplitude reached a maximum before frequency during locomotion, and when slowing down amplitude decreased and frequency was relatively unaffected.…”
Section: Figurementioning
confidence: 95%
“…More precisely, the theta rhythm induced by rotation is sensitive to atropine (Type 2 Theta) (Shin, 2010) and most probably linked to the cholinergic neurons of the medial septum (Tai et al, 2012). In cats and dogs, passive translation does not increase the power but increases the peak frequency of theta (Arnolds et al, 1984). Moreover, vestibular lesions decrease the power and the frequency of theta (Russell et al, 2006; Neo et al, 2012; Tai et al, 2012).…”
Section: The Pathway From the Nucleus Reticularis Pontis Oralis To Tmentioning
confidence: 99%